Experimental research on seismic behavior of concrete-filled reactive powder concrete tubular columns. (15th April 2021) - Shan, B.; Liu, G.; Li, T.Y.; Liu, F.C.; Liu, Z.; Xiao, Y.
Highlights: A noval concrete-filled reactive powder concrete tube (CFRPCT), was experimentally studied. CFRPCT columns showed significantly improved seismic behavior and lower residual deflection. Combination of high strength concrete with the CFRPCT hybrid system is favorable. Abstract: Concrete-filled reactive powder concrete (RPC) tube (CFRPCT) is a cement-based tubular composite column system, which combines the excellent compressive strength and the toughness of RPC and the lateral confining action from hoops. The novel composite system has the potential to be used in severe environment. To evaluate the seismic performance of CFRPCT columns, a series of low-cycle lateral loading tests were performed on eight model columns, including a bench-mark conventional reinforced concrete specimen and seven CFRPCT model columns, subjected to combine constant axial load and quasi-statically applied cyclic lateral loading. Volumetric hoop ratio, configuration of hoops, compressive strength of inner concrete and lateral loading procedure were selected as test parameters. Experimental results show that contrast to conventional hoop-confined concrete column, the failure of CFRPCT columns is characterized with well distributed cracks, without severe RPC cover spalling or crushing. The CFRPCT columns exhibited significantly higher initial stiffness, lateral load carrying capacity, ultimate lateral displacement, energy dissipation and smaller residual deformation as compared with those of the control column. An analytical model was also proposed for predicting the flexural strength of CFRPCT columns by considering the confinement effects.